Pengaruh Sikap Keuangan dan Pengetahuan Keuangan Terhadap Perilaku Manajemen Keuangan Mahasiswa Fakultas Ekonomi Pendidikan Bisnis Universitas Negeri Medan Angkatan 2023 - Leonardo Marcellinus Ndraha; Lenti Susanna Saragih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the influence of financial attitudes and financial knowledge on the financial management behavior of students in the Faculty of Economics, Business Education Study Program, Medan State University, Class of 2023. This research uses a quantitative method with an associative approach. The research sample consisted of 63 students selected using the total sampling technique. The instrument used was a Likert scale questionnaire, and the data were analyzed using multiple linear regression. The research results indicate that financial attitude has a positive and significant effect on financial management behavior, and financial knowledge also has a positive and significant effect. Simultaneously, financial attitudes and financial knowledge have a significant positive influence on students' financial management behavior. Thus, the better the financial attitude and financial knowledge possessed by students, the better their behavior in managing personal finances.